Once Weekly Whole-Body Electromyostimulation Enhances Muscle Quality in Men: Data of the Randomized Controlled Franconian Electromyostimulation and Golf Study - Zink-Rückel, Carina; Chaudry, Oliver; Engelke, Klaus; Ghasemikaram, Mansour; Kohl, Matthias; Uder, Michael; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
Whole-body electromyostimulation (WB-EMS) is commercially advertised as a time efficient resistance-type exercise technology. Indeed, the commercial, non-medical setting applied once weekly 20 min of WB-EMS only. However, this setting conflicts with the approved scientific approach that applied higher training frequencies. Using data from an ongoing study on WB-EMS and golf performance as a vehicle, we evaluate the effect of once weekly WB-EMS on changes of fatty muscle infiltration, as a crucial parameter of muscle quality. Fifty-four moderately physically active male amateur golfers 18-70 years old, were randomly allocated to a WB-EMS- (n=27) with a standard setting of once weekly 20 min and a non WB-EMS control group (CG, n=27). Intermuscular adipose tissue (IMAT) volume and intrafascial muscle tissue volume (MT) per unit of intrafascial volume as determined by magnetic resonance imaging were used to characterize muscle quality. Intention to treat analysis with multiple imputation was applied. WB-EMS was conducted at the participants' homes, thus attendance rate was close to 100%. After 16 weeks of intervention, we observed increases in volume-adjusted IMAT (p = 0.040) and decreases in MT (p = 0.206) in the CG. IMAT decreased in the WB-EMS group (p = 0.215), while MT increased significantly (p = 0.032). Of importance, group difference (i.e. “effects”) for intra-group changes in volume adjusted IMAT (effect size: d`=.66; p = 0.028) and MT (d`=.70; p = 0.020) were significant for both parameters. Once weekly WB-EMS application significantly affects muscle quality of the mid-thigh in moderately active, healthy men 18-70 years old.